Letter to the Editor—A Method for Obtaining the Optimal Dual Solution to a Linear Program Using the Dantzig-Wolfe Decomposition - Walker, Warren E. (Operations Research, 1969)
It is well known that the dual variables of a linear program may be obtained easily if the simplex method is vised to solve the problem. This note shows how to obtain these dual variables if the problem is solved by using the Dantzig-Wolfe decomposition principle.